Effect of Chronic Caffeine Consumption on Cardiac Tissue Metabolism in the Rabbit (Nigerian Journal of Physiological Sciences, 2021)
Summary: Previous studies on the ability of caffeine to enhance endurance and boost performance have focused on the energy substrates that are utilized by the skeletal muscle and the brain but nothing of such has been reported on cardiac tissue. This study was designed to investigate the effect of caffeine on cardiac tissue metabolism in the rabbit. The study was carried out on adult male New Zealand rabbits divided into 3 groups (n=5). Group I rabbits served as control and were given 0.5ml/Kg of normal saline while group II and III rabbits were administered with 2mg/Kg and 6mg/kg of caffeine respectively for 28 days. Blood samples were collected by retro orbital puncture for biochemical analysis. Animals were sacrificed by cervical dislocation and cardiac tissue biopsies were collected for biochemical and immunohistochemical analysis. Cardiac tissue glycogen concentration was determined by anthrone reagent method. Cardiac tissue CPT 1 activity and cAMP concentration were determined by immunohistochemistry and colorimetry techniques respectively, with assay kits obtained from Biovision Inc. The results showed that Caffeine at 2 and 6 mg/kg significantly inhibited MPO activity from 0.72±0.05 to 0.164±0.045 and 0.46±0.12 U/L respectively (p